The Influence Of Leadership Style, Motivation, And Work Environment On Employee Performance At Pt Jasindo Testing Services - Dolly Maulidin Hasibuan; Melfrianti Romauli Purba; Nasib Nasib (STIE Amkop Makassar, 2026)
The phenomenon that occurs in various companies shows that there are still many employees who experience decreased work enthusiasm, low productivity, and lack of satisfaction with the work environment. This study aims to further analyze the influence of leadership style, work motivation, and work environment on employee performance. The study used a quantitative method carried out at PT Jasindo Testing Service with a sampling method using the slovin technique with an error rate of 5%, resulting in 110 respondents from a total population of 151 people. Based on the results of the study that has been conducted, it can be concluded that Leadership Style (X1), Motivation (X2), and Work Environment (X3) have a significant influence on Employee Performance (Y) at PT Jasindo Testing & Inspection Services. This is evidenced by the significance value of 0.000 <0.05, and the Fcount value (244.975) > Ftable (2.69), which shows that the three independent variables simultaneously affect the dependent variable. In addition, the R-square value of 0.874 indicates that 87.4% of the variation in employee performance can be explained by leadership style, motivation, and work environment, while 12.6% is influenced by other factors not examined in this study. Thus, the better the leadership style, motivation, and work environment, the higher the employee performance.